Penentuan Produk Unggulan dari Olahan Susu Segar di Kecamatan Ciwidey, Jawa Barat - Bunga Cahyaputri; Hanik Atus Sangadah (Jurnal Optimalisasi, 2022)
Ciwidey is one of the fresh milk production areas with many tourist attractions has the potential to be developed, especially in the sale of processed milk products. The four processed whole milk products produced in Ciwidey are fresh milk, candy, yogurt, and greek. The purpose of this study is to determine the added value and the level of profit generated from the fresh milk processing business and to determine the superior processed products that are a priority to be developed in Ciwidey. The method used in this research is value added analysis using the Hayami method. The components of the calculation of the Hayami method are output, input, price, and income which give the results of conversion factors, labor coefficients, product values, value added ratios, labor benefits, other input contributions, and profit levels and margins. The results of the analysis show that there is added value from the production process of fresh milk, caramel milk candy, yogurt, and Greek, respectively, amounting to IDR 1.396/kg; IDR 21,141/kg; IDR 18,398/kg; and IDR. 69,947/kg. The biggest profit rate for fresh milk products is 98%. Yogurt and Greek products have the same profit rate of 89-90%. The lowest profit rate for candy products is 75%. The selected pure milk product is greek because the highest value of the added value, added value ratio, direct labor income, and the profit compared to the other 3 pure milk products.